2020
DOI: 10.1177/1464884920944741
|View full text |Cite
|
Sign up to set email alerts
|

Interest matters: The effects of constructive news reporting on Millennials’ emotions and engagement

Abstract: News media seem to have insufficient knowledge on how to reach Millennials. An important question is how professional journalism can prevent the disillusion that a growing number of Millennials experience when consuming news. Constructive journalism is often propagated as a way to improve the well-being and engagement of readers. To test this, the current study investigated the effects of constructive news on emotions and online engagement. In an experiment, 20–40-year-old participants ( n = 341) read a story … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 40 publications
(100 reference statements)
5
22
0
1
Order By: Relevance
“…It encompasses local and international information including religion, politics, technology, and entertainment. Through this style, Folkative influenced the followers particularly millennials to stay updated waiting for new upcoming posts on the topic which is relevant to their lives (Hermans & Prins, 2020). This current study empirically supports positive engagement happens not only because of news interest but also the way the news is reported (Drok et al, 2018).…”
Section: Discussionsupporting
confidence: 69%
“…It encompasses local and international information including religion, politics, technology, and entertainment. Through this style, Folkative influenced the followers particularly millennials to stay updated waiting for new upcoming posts on the topic which is relevant to their lives (Hermans & Prins, 2020). This current study empirically supports positive engagement happens not only because of news interest but also the way the news is reported (Drok et al, 2018).…”
Section: Discussionsupporting
confidence: 69%
“…Focusing on negative news only, Szabo and Hopkinson (2007) found that exposure to such news negatively affected the mood of participants, an effect that could be moderated by relaxation techniques. Furthermore, as noted above, a study by Hermans and Prins (2022) has shown that in comparison to those who read traditional news, readers of news deliberately written to be constructive (inclusion of positive emotion words, mentions of solutions to issues) reported higher levels of positive emotions.…”
Section: The Current Studymentioning
confidence: 86%
“…Adding a silver-lining to an otherwise negative story can also alleviate the increase in negative emotions felt after consuming otherwise negative news ( McIntyre and Gibson, 2016 ). Following this line of reasoning, research has found that readers of news deliberately written to be constructive had higher positive emotions than readers of more traditional news ( Hermans and Prins, 2022 ).…”
Section: Emotions In the Newsmentioning
confidence: 98%
“…The authors note the parasocial capacities of podcasts, which may increase constructive behaviours in public health (Lindgren and Jorgensen, 2023). Constructive journalism is proposed to increase audience engagement with, and trust in, news and information (van Antwerpen et al, 2022) and decrease negative emotions (Baden et al, 2019; Hermans and Prins, 2020; McIntyre and Gibson, 2016; McIntyre, 2017). These constructive journalistic practices may be amplified in podcasting given its manner of engaging with audiences.…”
Section: The Rise Of News Podcasts and Its Implications: Focusing On ...mentioning
confidence: 99%